2009
DOI: 10.1177/0093854809333958
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic Traits and Perceptions of Victim Vulnerability

Abstract: This study examines whether psychopathic traits in a nonreferred (and presumably nonpsychopathic) sample could enhance the accuracy of perceptions of victim vulnerability. In a previous study, the interpersonal and affective component of psychopathy was associated with increased accuracy in assessing vulnerability in dyadic conversations, and Grayson and Stein (1981) established that vulnerability could be assessed by observing targets walking. The purpose of this study was to determine whether individuals sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
132
8
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(159 citation statements)
references
References 56 publications
15
132
8
4
Order By: Relevance
“…Rather, we believe that our findings fail to support the conceptualization of psychopathy as a mental disorder and instead provide support for the notion that psychopathy may, in some form or another, have an adaptive function. Our findings fit well within the body of work showing that psychopathy: (1) is not associated with the neurodevelopmental perturbations characteristic of other serious mental disorders (Harris et al, 2001a, 2007b; Lalumière et al, 2001); (2) is positively associated with successful social exploitation (Mokros et al, 2008), the detection of emotions (Book et al, 2007), and the prediction of victim vulnerability (Wheeler et al, 2009); (3) is positively associated with mating effort and related patterns of sexual behavior (Quinsey et al, 1995; Lalumière and Quinsey, 1996; Harris et al, 2007b); (4) shows no negative (and shows perhaps even a positive) effect on reproductive success (Harris et al, 2007b; Pulkkinen et al, 2009; Vachon et al, 2012); and (5) is associated with an increased likelihood of offending in instrumental ways (Williamson et al, 1987; Cornell et al, 1996). Nonetheless, further research testing hypotheses of “special design” will be necessary to continue to build the case for psychopathy as an adaptation.…”
Section: Discussionsupporting
confidence: 87%
“…Rather, we believe that our findings fail to support the conceptualization of psychopathy as a mental disorder and instead provide support for the notion that psychopathy may, in some form or another, have an adaptive function. Our findings fit well within the body of work showing that psychopathy: (1) is not associated with the neurodevelopmental perturbations characteristic of other serious mental disorders (Harris et al, 2001a, 2007b; Lalumière et al, 2001); (2) is positively associated with successful social exploitation (Mokros et al, 2008), the detection of emotions (Book et al, 2007), and the prediction of victim vulnerability (Wheeler et al, 2009); (3) is positively associated with mating effort and related patterns of sexual behavior (Quinsey et al, 1995; Lalumière and Quinsey, 1996; Harris et al, 2007b); (4) shows no negative (and shows perhaps even a positive) effect on reproductive success (Harris et al, 2007b; Pulkkinen et al, 2009; Vachon et al, 2012); and (5) is associated with an increased likelihood of offending in instrumental ways (Williamson et al, 1987; Cornell et al, 1996). Nonetheless, further research testing hypotheses of “special design” will be necessary to continue to build the case for psychopathy as an adaptation.…”
Section: Discussionsupporting
confidence: 87%
“…Wheeler, Book, and Costello (2009) found that male college students scoring high on self-reported Factor 1 psychopathic traits were more accurate at perceiving vulnerability in potential victims. The authors believed this was due to manipulation and superficial charm, and the assumed related ability to decode body movement cues.…”
Section: Individual Differences and First Impressionsmentioning
confidence: 90%
“…In one exception, those higher in psychopathy showed a shift in brain activation towards strategic cooperation only when playing a repeated prisoner's dilemma game (PD) with an in-group member [23], suggesting sensitivity to partner value. Consistent with a complementary sensitivity, those higher in subclinical primary psychopathy are especially perceptive of potential victim vulnerability [35].…”
Section: Introductionmentioning
confidence: 88%